(untitled) (Annals of Medical Research, 2022)
Aim: The aim of this study was to investigate the correlation of C-reactive protein (CRP), neutrophil to lymphocyte ratio (NLR), platelet to lymphocyte ratio (PLR), and red cell distribution width (RDW) in patients with idiopathic carpal tunnel syndrome (CTS). Materials and Methods: One hundred patients with CTS and 60 control subjects were included in this study. Medical records and laboratory findings of the participants were analyzed retrospectively between March 2019 and February 2020. Laboratory result values obtained from the members included in the study were examined. Results: There was a correlation between CRP and the severity of CTS (p<0.01). There was also a positive correlation between CRP and symptom severity scale (p<0.01) and functional status scale (p<0.01). No statistically significant changes were observed in the measurements of blood values other than CRP in the patients. Conclusion: In this study, a relationship was found between CRP, one of the hematological parameters, and the presence or severity of CTS.